Association between periodontal disease, preterm birth and low birth weight - Patrícia Nienkotter Sad Silva; Tatiana Miranda Deliberador; Marilisa Carneiro Leão Gabardo; Flares Baratto-Filho; Eduardo Pizzatto (Editorial Ciencias Médicas, 2018)
Objective: evaluate the association between periodontal disease, preterm births and low birth weight neonates in a group of women from the city of Curitiba, PR, Brazil. Methods: in this case-control study, an evaluation was conducted of 51 mothers aged 16-40 years divided into two groups: those with a preterm delivery and low birth weight babies, and those without a preterm delivery but with low birth weight babies. Data about the mothers and the neonates were collected via questionnaires and medical record analysis. Periodontal examination was performed at six sites of each tooth present, except for the third molars. Results: it was found that 82.4 % of the women had had a normal delivery and 25.5 % a preterm delivery. 19.6 % of the babies weighed less than 2 500 g at birth, and 5.9 % of the women had periodontal disease. Conclusions: no association was found in the sample between periodontal disease and preterm delivery and low birth weight.